'Green' nanotherapeutics from tea leaves for orally targeted prevention and alleviation of colon diseases. (December 2021) - Zu, Menghang; Xie, Dengchao; Canup, Brandon S.B.; Chen, Nanxi; Wang, Yajun; Sun, Ruxin; Zhang, Zhan; Fu, Yuming; Dai, Fangyin; Xiao, Bo
Abstract: Although synthesized nanotherapeutics (NTs) are attractive for the oral treatment of colon diseases, their clinical translations are constrained by the unsatisfactory therapeutic outcomes, potential adverse effects, and high cost of mass production. Here, we report the development of tea leaf-derived natural NTs with desirable particle sizes (140.0 nm) and negative surface charge (−14.6 mV). These natural exosome-like NTs were found to contain large amounts of lipids, some functional proteins, and many bioactive small molecules. Specifically, galactose groups on the surface of NTs could mediate their specific internalization by macrophages via galactose receptor-mediated endocytosis. Moreover, these NTs were able to reduce the production of reactive oxygen species, inhibit the expression of pro-inflammatory cytokines, and increase the amount of anti-inflammatory IL-10 secreted by macrophages. Orally administered NTs could efficiently inhibit the inflammatory bowel responses, restore disrupted colonic barriers and enhance the diversity and overall abundance of gut microbiota, thereby preventing or alleviating inflammatory bowel disease and colitis-associated colon cancer. The present study brings new insights to the facile application of a versatile and robust natural nanoplatform for the prevention and treatment of colon diseases. Graphical abstract: Image 1